Dimensi Kesalehan Sosial Dalam Tafsir al-Iklil fi Ma’ani al-Tanzil Karya Misbah Zain al Musthafa - Abd Majid Abror (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract The individual righteousness referred to is a righteousness that only takes care of worship solely as it relates to God and self-interest, while social righteousness is understood as righteousness that demonstrates the behavior of people who care about Islamic values, which are social. The dimension of social righteousness which is poured by KH Misbah Zain al-Mustafa in his commentary on Al Iklil fi Ma'ani at-Tanzil as a solution to the phenomenon of social inequality in daily life and can be enshrined in a contemporary era, including 1) Brotherhood of fellow man: Ukhuwah Insaniyatih; 2) Brotherhood and Marriage: Ukuwah Nasabiyah Shihriyah; 3) Brotherhood of tribe and Nation: Ukhuwah Sya'biyah Wathaniyah; 4) The Brotherhood of fellow believers: Ukhuwah Diniyah; 5) The Sisterhood-Seagama: Ukhuwah Imaniyah.